An Act Reducing into One and Amending the Several Acts Respecting the Removal of Nuisances, § 23, ALEXANDRIA, CHARTER & REVISED LAWS (Rounsavell and Pittman 1821). - (:unkn) unknown (General Publisher, 1821)
That no person shall discharge any musket, fowling piece, pistol, or other fire arms, or any composition of gun powder, or fulminating powder, within the limits of the town of Alexandria, unless in the execution of some law, or in the discharge of some duty imposed by law. Every person ofiending herein, shall forfeit and pay one dollar for each offence."
--
Keywords: DISCHARGE